REVIEW OF COASTAL CHARACTERISTICS OF IRON SAND DEPOSITS IN CILACAP CENTRAL JAVA - Hananto Kurnio (BULLETIN OF THE MARINE GEOLOGY, 2007)
Mineable iron sand deposits in Cilacap â€“ southern coastal area of Central Java have certain coastal characteristics that need to be studied in order to understand its depositional environment. With the knowledge of such environment, it can be applied to look for other places prospective of iron sand deposits that have the same characteristics especially recently when Cilacapâ€™s deposits were almost depleted. Coastal characteristics of iron sand deposit in Cilacap is shown by successive sandy beach ridges separated by marshy valleys typical of prograded coasts and by dunes of sand elongated parallel to the shore line with elevation varies from 0 m to 15 m above sea level. The iron sand deposit was derived from denudation of andesite and â€œOld Andesite Formationâ€ enriched in magnetite and ilmenite minerals in the steep elevated and deeply weathered rock hinterlands of Cilacap. High sediment loads of Serayu Basin in the hinterland (3,500-4,500 ton/km2/year; Citarum River basin only 800-1,200 ton/km2/year) was causing extensive deposition of iron sand in the coastal zone. Key words: coast, characteristic, iron sand, Cilacap Endapan pasir besi yang dapat ditambang di Cilacap â€“ pesisir selatan Jawa Tengah memiliki karakteristik pantai tertentu yang perlu dikaji agar dapat dipahami lingkungan pengendapannya. Dengan pengetahuan tentang lingkungan pengendapan tersebut, dapat diterapkan untuk mencari daerah-daerah lain prospek endapan pasir besi yang memiliki karakteristik yang sama terutama pada akhir-akhir ini ketika endapan Cilacap akan habis. Karakteristik pantai endapan pasir besi di Cilacap dicirikan oleh urutan pematang pantai berpasir yang dipisahkan oleh lembah-lembah berawa khas pantai maju dan oleh gumuk-gumuk pasir memanjang sejajar dengan garis pantai dengan ketinggian bervariasi dari 0 m hingga 15 m dari muka laut. Endapan pasir besi di daerah ini berasal dari proses denudasi andesit dan â€œFormasi Andesit Tuaâ€ yang kaya akan mineral magnetit dan ilmenit pada pedalaman Cilacap dengan kondisi elevasi curam dan batuan sangat terlapukkan. Muatan sedimen yang tinggi dari Cekungan Serayu di pedalaman tersebut (3.500-4.500 ton/km2/tahun; cekungan Sungai Citarum hanya 800-1.200 ton/km2/tahun) menyebabkan pengendapan yang sangat luas pasir besi di wilayah pantai. Kata kunci: pantai, karakteristik, pasir besi, Cilacap